Mengeksplorasi Dasar-Dasar Genetik Perundungan: Analisis Kontemporer terhadap Kajian Ilmiah - Shahzad Ali; Nurul Hartini; Nono Hery Yoenanto; Pramesti Pradna Paramita (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
Since the early 21st century, bullying has been a central focus for scholars, with various forms, such as relational, physical, cyber, and social bullying, receiving extensive attention. However, the role of genetic and hereditary factors in bullying remains underexplored. This study systematically reviews 31 scholarly articles published between January 2000 and December 2021. Articles were selected based on predefined inclusion criteria, including methodological rigor, relevance to genetic influences on bullying, and clear population samples. Data sources included Google Scholar, ResearchGate, SAGE Journals, and ERIC, with keywords such as “bullying and genetics,” “bullying and hereditary,” and “family genetics involvement.” The findings reveal significant associations between genetic predispositions and bullying behaviors. For example, genetic factors were found to account for approximately 70–77% of bullying perpetration and victimization in multiple studies, highlighting a strong hereditary influence. Traits such as impulsivity and aggression, often linked to genetic predispositions, were also shown to interact with environmental factors such as family dynamics and peer relationships, amplifying bullying tendencies. These results underscore the critical role of genetic and hereditary transmission in shaping bullying behaviors across generations. The study emphasizes the need for a multidisciplinary approach that integrates genetic research with environmental interventions to address bullying effectively. Practical implications include the development of targeted anti-bullying programs that consider individual genetic susceptibility alongside fostering supportive family and school environments to reduce the intergenerational transmission of bullying behaviors.